2015
DOI: 10.1093/chromsci/bmv126
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Determination of Clenbuterol in Pork by Direct Immersion Solid-Phase Microextraction Coupled with Gas Chromatography–Mass Spectrometry

Abstract: Direct immersion solid-phase microextraction (DI-SPME) coupled with gas chromatography-mass spectrometry (GC-MS) was developed for rapid analysis of clenbuterol in pork for the first time. In this work, a low-cost homemade 44 µm polydimethylsiloxane (PDMS) SPME fiber was employed to extract clenbuterol in pork. After extraction, derivatization was performed by suspending the fiber in the headspace of the 2 mL sample vial saturated with a vapor of 100 µL hexamethyldisilazane. Lastly, the fiber was directly intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…The procedure was performed by suspending the fiber in the HS of a vial saturated with the derivatization reagent. 240 As previously mentioned, the contamination of meat samples can also derive from food packaging materials. In this regard, a multiple HS SPME approach was adapted in a migration study to quantitatively assess contaminants from self-stick labels in fresh sausage samples.…”
Section: ■ Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The procedure was performed by suspending the fiber in the HS of a vial saturated with the derivatization reagent. 240 As previously mentioned, the contamination of meat samples can also derive from food packaging materials. In this regard, a multiple HS SPME approach was adapted in a migration study to quantitatively assess contaminants from self-stick labels in fresh sausage samples.…”
Section: ■ Applicationsmentioning
confidence: 99%
“…In cases where DI-SPME was used with coatings not compatible with complex food matrixes, additional sample pretreatment steps such as centrifugation and supernatant collection, dilution, or filtration were also necessary in order to obtain clean extracts and preserve coating integrity. Among the commercial SPME coatings classically used for DI-SPME in complex matrixes, the most used and suitable to withstand direct exposure in complex food media are PDMS coatings . Several studies have shown that PDMS SPME coatings, in comparison to other commercially available coatings, are more inert toward irreversible fouling caused by food matrix components due to their nonporous, smooth surface, which helps avoid irreversible attachment of nonvolatile macromolecules. , On the other hand, other commercially available coatings were shown to suffer precocious deterioration after direct exposure to such matrixes due to the rough and porous surface imposed by sorptive particles. However, such particles provide substantially higher extraction capacities than pure PDMS. ,, Aiming to merge the antifouling properties of PDMS with the higher extraction efficiency of sorptive particles often used for SPME, e.g., DVB, a new matrix compatible coating, PDMS/DVB/PDMS, was developed as described in the section corresponding to Biocompatible SPME Coatings.…”
Section: Applicationsmentioning
confidence: 99%
“…SPME was used to determine clenbuterol in pork using GC-MS, with 97.4–105.7% recovery ( Ye et al, 2016 ), and neurotransmitters in bovine tissue using LC-MS/MS ( Lendor et al, 2019 ). SPME was used for direct analysis in real time, coupled to tandem mass spectroscopy, for rapid and high-throughput screening of multi-residue pharmaceuticals in bovine tissue.…”
Section: Applicationsmentioning
confidence: 99%
“…In recent decades, a variety of analytical methods for detecting β 2 -agonists has been developed, such as high-performance liquid chromatography (HPLC) [ 7 ], gas chromatography–mass spectrometry (GC-MS) [ 8 ], liquid chromatography–mass spectrometry (LC-MS) [ 9 ], liquid chromatography–tandem mass spectrometry (LC-MS/MS) [ 10 ], capillary electrophoresis electrochemical detection [ 11 ], colorimetric ELISA [ 12 ], and other analytical methods. Although large instrumental methods can accurately detect complex samples, they often require time-consuming procedures, expensive instruments, and skilled technicians and are not suitable for rapid screening and onsite analyses [ 13 ].…”
Section: Introductionmentioning
confidence: 99%